Investigation of personal variables, technology usage, vaccine-related variables, social media-specific epistemological beliefs, media literacy, social impact strategies variables affecting vaccine hesitancy beliefs in the Covid-19 pandemic. - Yildiz Durak, Hatice; Şimşir Gökalp, Zeynep; Saritepeci, Mustafa; Dilmaç, Bülent; Durak, Aykut (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Aim: In this study, personal variables, technology use cases, vaccine-related variables, social media-specific epistemological beliefs, media literacy, and social influence strategies were examined as predictors of Covid-19 vaccination hesitancy (VH) beliefs. Subject and methods: The prediction design research model is used to detect the predictors of the dependent variable. The study group consists of 378 participants. Five different scales were used together with the self-description form as a data collection tool. Results: According to the results of the research, individuals who have positive perceptions about the safety of Covid-19 vaccines and who have received the Covid-19 vaccine have lower anti-vaccine beliefs. It is another situation that prevents the opposition to vaccination of those who research the source of information on social media. As a result, age, education and income level, social media usage experience, media literacy, and social influence strategies were not effective on the participants' anti-vaccine beliefs. Conclusion: According to the findings of the study, positive perceptions about the safety of Covid-19 vaccines, being vaccinated against Covid-19, and researching a source of information on social media variables seem to be effective in laying the foundations for constructive interventions such as using anti-vaccine beliefs to guide, reduce or eliminate negative beliefs about vaccines.